1996
DOI: 10.1002/stem.5530140704
|View full text |Cite
|
Sign up to set email alerts
|

Early Suppressive Effects of Chemotherapy on Recovery of Bone Marrow Megakaryocyte Precursors: Possible Relationship to Platelet Recovery

Abstract: Abstract. This study utilized a recently developed culture and quantitation system to detect megakaryocyte precursors in CD34' bone marrow cells from normal donors and breast cancer patients treated with 5-fluorouracil, leucovorin, adriamycin and cyclophosphamide (FLAC). Bone marrow was obtained from patients before and then after their first cycle of FLAC once blood cell counts had reeovered. CD34+ cells were isolated and placed in liquid culture with growth factors to stimulate proliferation and lineage comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Damage to the progenitor/stem cell compartment or the marrow microenvironment or both has been implicated as potential causes for the reduced capacity of post-chemotherapy LTC to support hematopoiesis. 7,19,21,23,24,26,27 In the present study, stromal layers established from post-chemotherapy marrow were cocultured with normal * * * Anti-TNF-␣ effects on CFU-GM numbers in cocultures of normal donor CD34 + cells with GM-CSF and PIXY321 pretreated stromal layers. Established stromal layers were irradiated to eliminate residual hematopoietic progenitors, and the following day the media were changed and DPBS or 20 ng/ml PIXY321 or GM-CSF was added to the cultures.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Damage to the progenitor/stem cell compartment or the marrow microenvironment or both has been implicated as potential causes for the reduced capacity of post-chemotherapy LTC to support hematopoiesis. 7,19,21,23,24,26,27 In the present study, stromal layers established from post-chemotherapy marrow were cocultured with normal * * * Anti-TNF-␣ effects on CFU-GM numbers in cocultures of normal donor CD34 + cells with GM-CSF and PIXY321 pretreated stromal layers. Established stromal layers were irradiated to eliminate residual hematopoietic progenitors, and the following day the media were changed and DPBS or 20 ng/ml PIXY321 or GM-CSF was added to the cultures.…”
Section: Discussionmentioning
confidence: 92%
“…22,26 Damage to either the hematopoietic progenitor/stem cell compartment or the marrow microenvironment or both has been implicated as a potential cause for suppressive effects of bone marrow function observed after chemotherapy. 7,19,21,23,24,26,27 A variety of stimulatory and negative factors that regulate the proliferation and differentiation of hematopoietic progenitors are expressed in the marrow microenvironment. 6,[28][29][30] Two of the possible causes for hematopoietic deficiencies observed after chemotherapy are either a decrease in production of stimulatory factors or an increase in the production Table 1 Recovery of committed and primitive progenitors in post-chemotherapy marrow CD34 + cells …”
mentioning
confidence: 99%
“…It was shown that decrease in stem cell numbers after chemo‐ and radiotherapy exposures directly affect PLT count. In addition, decrease in maturation from altered marrow environment, accessory cells, and growth factor levels affect megakaryocyte maturation, PLT release, and their migration into circulation 19,20 …”
mentioning
confidence: 99%
“…In other group II patients, depletion of the Mk pool may have been a result of increased sensitivity to chemotherapy-induced BM damage. 39 However, not all group II patients had reduced numbers of Mk progenitors in the PBPC autograft. Four patients mobilized and received large numbers of Mk progenitors similar to group I.…”
Section: Discussionmentioning
confidence: 98%